2013
DOI: 10.1002/ase.1353
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of virtual microscopy in medical histology teaching

Abstract: Histology stands as a major discipline in the life science curricula, and the practice of teaching it is based on theoretical didactic strategies along with practical training. Traditionally, students achieve practical competence in this subject by learning optical microscopy. Today, students can use newer information and communication technologies in the study of digital microscopic images. A virtual microscopy program was recently introduced at Ghent University. Since little empirical evidence is available c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
0
5

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(57 citation statements)
references
References 31 publications
0
52
0
5
Order By: Relevance
“…Braun and Kearns () reported that virtual microscopy provided increased learning efficiency and student collaboration in learning pathology, compared with prior optical microscopy methods. Mione et al () provided controlled cross‐over study evidence that student learning performance with virtual microscopy is comparable to that with optical microscopy, for acquiring image‐based knowledge in medical histology. Digital slide collections and “virtual microscopy” have become more widely accepted for use in microscopic anatomy laboratory instruction (Pinder et al, ; McBride and Prayson, ; Gatumu et al, ), and a recent American Association of Anatomists' survey showed that a majority of respondent institutions used virtual microscopy alone or in conjunction with microscopes (Drake et al, ).…”
Section: Three‐dimensional Simulation Modeling and Virtual Realitymentioning
confidence: 99%
“…Braun and Kearns () reported that virtual microscopy provided increased learning efficiency and student collaboration in learning pathology, compared with prior optical microscopy methods. Mione et al () provided controlled cross‐over study evidence that student learning performance with virtual microscopy is comparable to that with optical microscopy, for acquiring image‐based knowledge in medical histology. Digital slide collections and “virtual microscopy” have become more widely accepted for use in microscopic anatomy laboratory instruction (Pinder et al, ; McBride and Prayson, ; Gatumu et al, ), and a recent American Association of Anatomists' survey showed that a majority of respondent institutions used virtual microscopy alone or in conjunction with microscopes (Drake et al, ).…”
Section: Three‐dimensional Simulation Modeling and Virtual Realitymentioning
confidence: 99%
“…This would enable exploration of whether high-performing students benefit more or less from a collaborative approach than low-performing students, as has been suggested previously [15]. The administration of a pre-intervention test would also provide a baseline level for comparison with the post-intervention results [55]. …”
Section: Discussionmentioning
confidence: 99%
“…While virtual microscopy represented a highly innovative milestone in medical education (Gatumu, et al, ; Wilson et al, ), and has been associated with equivalent or improved mastery of medical histopathology (Krippendorf and Lough, ; Bloodgood and Ogilvie, ; Braun and Kearns, ; Triola and Holloway, ; Mione et al, ; Tian et al, ), it did not resolve a major drawback in histopathology training—namely, a lack of student engagement during laboratory sessions that had been noted empirically at other medical schools (Black and Smith, ) as well as at UT‐Health, San Antonio. Student frustration occurred at multiple levels including difficulties in locating and identifying specific cells or tissues, correlating microscopic observations with other content in a given module, and appreciating the importance of histopathology in the clinical practice of medicine.…”
Section: Introductionmentioning
confidence: 99%